Expression of dementia biomarkers in Appalachian and non-Appalachian ELVO patients during thrombectomy - Anil, Neha; McLouth, Christopher J.; Hazelwood, Hunter S.; Dahlke, Elise; Frank, Jacqueline A.; Millson, Nathan; Al-Kawaz, Mais; Harp, Jordan P.; Cranford, Will; Pahwa, Shivani; Dornbos, David; Fraser, Justin F.; et al. (Frontiers in Neuroscience, 2025)
Background/ContextVascular Cognitive Impairment and Dementia (VCID) affects 25-30% of stroke patients and includes cognitive impairments caused by vascular injury, such as post-stroke dementia. Rehabilitation has the potential to improve the quality of life for patients at risk of developing dementia. However, there is currently no reliable method to identify those at risk of dementia after a stroke. Several biomarkers, including ADRD (Alzheimer’s disease and related dementias) biomarkers (Ab, tau, NfL, and GFAP) and angiogenic factors (VEGF, Flt-1, Tie-2, PIGF, and FGF) have been associated with the development of dementia.Populations in Appalachia experience a higher incidence of stroke and related mortality compared to other groups. Given the elevated stroke rates in Appalachian communities, this study aims to investigate potential proteomic differences between patients from Appalachian and non-Appalachian counties. The primary goal of the study is to characterize the expression of post-stroke cognitive dementia biomarkers and to explore differences in the proteomic profiles of Appalachian and non-Appalachian populations.Methods/ApproachSample Collection: The Blood and Clot Thrombectomy Registry Collaborative (BACTRAC) protocol, established by Fraser and colleagues, introduces a novel method for analyzing stroke by collecting intracranial blood samples from patients undergoing mechanical thrombectomy. During the procedure the thrombus and blood samples from areas distal and proximal to the thrombus are collected and undergo proteomic analysis (Fraser et al.). Additional demographic and clinical information are collected from electronic health records. The control data was obtained from arterial blood collected during diagnostic angiograms from patients with cerebrovascular disease.Data AnalysisPropensity score models were used to perform a one-to-one match between stroke and control patients on age, sex, BMI, hypertension, and hyperlipidemia resulting in groups that were balanced on these measured prognostic characteristics. A Wilcoxon rank sum test was then used to assess differences in the 12 ADRD biomarkers.ResultsCompared to the controls, stroke patients had significantly higher levels of GFAP. The control patients had significantly higher levels of AB40, AB42, and VEGFA. In the Appalachian patient population, the control patients also had significantly higher levels of AB40, AB42, and VEGFA. Additionally, the Appalachian stroke patients had higher GFAP. In the non-Appalachian population only GFAP was significantly different between stroke and control groups, with it being elevated in the stroke group.ConclusionThere was a notable difference in the levels of certain ADRD biomarkers between stroke patients and control patients. Specifically, in Appalachian populations, stroke patients showed significant differences in multiple ADRD biomarkers (AB40, AB42, and GFAP) compared to controls, a pattern not seen in non-Appalachian stroke patients, where only GFAP levels increased. This difference in ADRD biomarkers observed in Appalachian stroke patients could be attributed to a combination of socioeconomic and environmental factors unique to the Appalachian region.